2018
DOI: 10.1016/j.ecosys.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of exchange rate changes on the Malaysia-China commodity trade

Abstract: Previous research that considered the response of the trade balance between Malaysia and China to exchange rate changes used a linear model and did not find any significant long-run link. Suspecting that the results suffer from aggregation bias as well as ignoring nonlinear adjustment of the exchange rate, we consider the trade balance of 59 industries that trade between the two countries and use a nonlinear ARDL model to show that almost 1/3 rd of the industries are affected by ringgit depreciation against yu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…9 The …nding of negative relationship between domestic real income and trade balance is not surprising as increase in economic growth of Nigeria often lead to more increase in the importation of foreign goods which consequently deteriorate the trade balance due to large di¤erential between the import and export of the country. 10 This …nding is consistent with the …ndings of Adeniyi (2011), Eke et al (2015), Igue and Ogunleye (2014) and Dzanan and Masih (2017). 11 It should note that the graphical representation of the CUSM and CUSUMQ are not presented in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…9 The …nding of negative relationship between domestic real income and trade balance is not surprising as increase in economic growth of Nigeria often lead to more increase in the importation of foreign goods which consequently deteriorate the trade balance due to large di¤erential between the import and export of the country. 10 This …nding is consistent with the …ndings of Adeniyi (2011), Eke et al (2015), Igue and Ogunleye (2014) and Dzanan and Masih (2017). 11 It should note that the graphical representation of the CUSM and CUSUMQ are not presented in this study.…”
Section: Resultssupporting
confidence: 90%
“…The results of the parsimonious error correction model with lagged and current periods are also presented in Table 3. The estimated coe¢ cient of domestic real income is positively signi…cant in in ‡uencing trade balance in the short run 10 . Speci…cally, the …ndings show that a 1% increase in economic growth of Nigeria will improve the trade balance by 0.344% in the short run .Similarly, foreign real income adds signi…cantly to improvement in trade balance in the short run as expected, suggesting that a 1% increase in foreign real income leads to improvement in Nigeria's trade balance by 0.3% in the short run.…”
Section: Resultsmentioning
confidence: 91%
“…This is one of the most notable advantages of NARDL and ARDL models compared to traditional cointegration methods such as Johansen (1991) and Engle and Granger (1987) because they require that all variables must be I(1) processes. As a result, unit root tests are unnecessary because most of the macroeconomic variables are integrated of order 1 ( Bahmani-Oskooee et al, 2017 ; Bahmani-Oskooee and Aftab, 2018 ; Bahmani-Oskooee and Baek, 2018 ; Iyke and Ho, 2018 ; Bahmani-Oskooee and Nasir, 2019 ). In addition, ARDL method is still appropriate despite small sample size ( Odhiambo, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of J-curve effect, much more attention has been given to investigating the short-run and long-run impacts of exchange rate on trade balance ( Bahmani-Oskooee and Mitra, 2010 ). Nonetheless, many research report insignificant results, and the existing literature has identified 2 main culprits: aggregation bias and linear assumption ( Bahmani-Oskooee et al., 2016 ; Bahmani-Oskooee and Aftab, 2018 ; Iyke and Ho, 2018 ). First, although analyzing the impact of real effective exchange rate on the trade balance of a country with the rest of the world at aggregate level can be very convenient and present valuable information about her international trade as a whole, the findings may suffer from bias ( Rose and Yellen, 1989 ; Bahmani-Oskooee and Brooks, 1999 ; Phong et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study will adopt the VECM technique to measure both short-and long-run relationships if the tests found cointegration. Referring to Asteriou and Hall (2011) and Wang, Wu, and Yang (2014), the following VECM equation is estimated:…”
Section: Empirical Modelmentioning
confidence: 99%